Exploring Levels of Control for a Navigation Assistant for Blind Travelers - Ranganeni, Vinitha; Sinclair, Mike; Ofek, Eyal; Miller, Amos; Campbell, Jon; Kolobov, Andrey; Cutrell, Ed (HRI 2023, 2023)
Only a small percentage of blind and low-vision people use traditional mobility aids such as a cane or a guide dog. Various assistive technologies have been proposed to address the limitations of traditional mobility aids. These devices often give either the user or the device majority of the control. In this work, we explore how varying levels of control affect the users' sense of agency, trust in the device, confidence, and successful navigation. We present Glide, a novel mobility aid with two modes for control: Glide-directed and User-directed. We employ Glide in a study (N=9) in which blind or low-vision participants used both modes to navigate through an indoor environment. Overall, participants found that Glide was easy to use and learn. Most participants trusted Glide despite its current limitations, and their confidence and performance increased as they continued to use Glide. Users' control mode preference varied depending on the circumstances; no single mode "won" in all situations.